Réexamen du mobilier venant de l’épave d’un navire coulé par les pirates au XVIIIe siècle dans la baie d’Ambodifotatra, île Sainte-Marie, Madagascar - Jean Soulat; Yann von Arnim; Alexandre Audard; John de Bry; Alexandre Coulaud (Afriques)
Following on from the underwater archaeological investigations carried out between 2000 and 2015 in Ambodifotatra Bay on Sainte-Marie Island (Madagascar), a new mission aimed at uncovering the terrestrial remains of a pirate occupation also had the opportunity in May 2022 to re-examine all the artifacts from a wreck, a ship sunk by pirates whose identification has yet to be determined. Initially identified as the supposed Fiery Dragon, sunk in 1721, the wreck was photogrammetrically surveyed and two soundings were taken. The latter have yielded a large quantity of material, notably more than 2,800 fragments of Chinese porcelain, Southeast Asian ceramics, metal objects, glassware and archaeozoological remains. Packaged, sometimes desalinated, this collection was deposited in the Musée de la Reine Betia on îlot Madame. Nevertheless, no reliable inventory or study report has been submitted to the Malagasy authorities. This article, based on the report written in 2023 by the mission team, aims to reveal to the scientific community the interest of re-examining this exceptional furniture coming from a pirate context of the 18th century.